Numerical Study of Reactive Flow in Fractured Carbonate Rock - Zhou, Xu; Zhang, Qingfu; Xing, Hongchuan; Lv, Jianrong; Su, Haibin; Huang, Zhaoqin (Frontiers in Earth Science, 2021)
Acidizing technology is an effective measure to restructure oil and gas reservoirs, Moreover, it can also remove the reservoir pollution and connect the near-wellbore zone. The optimal injection rate of acid is one of key factors to reduce cost and improve the effect of acidizing. Therefore, the key problem is to find the optimal injection rate during acid corrosion in carbonate rock. A novel reactive flow mathematical model based on two-scale model and discrete fracture model is constructed in this study. The matrix system and the fracture system are described by two-scale model and discrete fracture model, respectively. This study firstly combines the two-scale model with the discrete fracture model. Then, numerical simulation is implemented by solving dimensionless equations. The corresponding numerical scheme based on Galerkin finite method was proposed. Several important problems are studied in this work, including the influence of injection rate of acid on the dissolution patterns, the influence of fracture aperture, and fracture orientations on the dissolution structure and the breakthrough volume of injected acid, the dynamic change of fracture aperture during acidizing is also studied. The numerical simulation results show that there is existing an optimal injection rate in fractured medium. The existence of fracture, the heterogeneity of initial fracture aperture and the dynamic change of fracture aperture will only have an impact on the dissolution structure of core and will not affect the optimal injection rate of acid.